Environmental performance and regional innovation spillovers - Valeria Costantini; Massimiliano Mazzanti; Anna Montini (Fondazione Eni Enrico Mattei (FEEM), 2010)
The achievement of positive environmental performance at national level could strongly depend on differences in local capabilities of both institutions and the private business sector. Environmental regulation alone is a weak instrument if the institutional and business environment cannot transform regulation strengths into opportunities. In this paper, we use the new environmental accounting matrix for polluting emissions now available for the 20 Italian Regions that covers 24 sectors and combines a shift-share approach with spatial econometric modelling. We provide evidence of the role played by internal innovation, innovation spillovers and regional policies in shaping the geographical distribution of environmental performance achievements.
Keywords: Q53; Q55; Q56; R15; 330; Environmental Performance; Technological Innovation; Regional Spillovers; Polluting Emissions; Italian Regions